The prognostic value of neutrophil-to-lymphocyte ratio in patients with traumatic brain injury: A systematic review - Ghozy, Sherief; El-Qushayri, Amr Ehab; Varney, Joseph; Kacimi, Salah Eddine Oussama; Bahbah, Eshak I.; Morra, Mostafa Ebraheem; Shah, Jaffer; Kallmes, Kevin M.; Abbas, Alzhraa Salah; Elfil, Mohamed; Alghamdi, Badrah S.; Ashraf, Ghulam; et al. (Frontiers in Neurology, 2022)
Traumatic brain injury (TBI) places a heavy load on healthcare systems worldwide. Despite significant advancements in care, the TBI-related mortality is 30–50% and in most cases involves adolescents or young adults. Previous literature has suggested that neutrophil-to-lymphocyte ratio (NLR) may serve as a sensitive biomarker in predicting clinical outcomes following TBI. With conclusive evidence in this regard lacking, this study aimed to systematically review all original studies reporting the effectiveness of NLR as a predictor of TBI outcomes. A systematic search of eight databases was conducted according to the Preferred Reporting Items for Systematic Review and Meta-Analyses statement (PRISMA) recommendations. The risk of bias was assessed using the Quality in Prognostic Studies (QUIPS) tool. Eight studies were ultimately included in the study. In most of the studies interrogated, severity outcomes were successfully predicted by NLR in both univariate and multivariate prediction models, in different follow-up durations up to 6 months. A high NLR at 24 and 48 h after TBI in pediatric patients was associated with worse clinical outcomes. On pooling the NLR values within studies assessing its association with the outcome severity (favorable or not), patients with favorable outcomes had 37% lower NLR values than those with unfavorable ones (RoM= 0.63; 95% CI = 0.44–0.88; p = 0.007). However, there were considerable heterogeneity in effect estimates (I2 = 99%; p < 0.001). Moreover, NLR was a useful indicator of mortality at both 6-month and 1-year intervals. In conjunction with clinical and radiographic parameters, NLR might be a useful, inexpensive marker in predicting clinical outcomes in patients with TBI. However, the considerable heterogeneity in current literature keeps it under investigation with further studies are warranted to confirm the reliability of NLR in predicting TBI outcomes.